Entre flores e espinhos: a atuação do técnico em enfermagem na estratégia saúde da família - Silva, Francisca Idanésia da (2008)
It is about a study of an exploratory/descriptive type with a qualitative approach whose aim was to analyze the actuation of nursing technicians in Family Health Strategy (FHS), taking into consideration the defined attributions by the Ministry of Health (MH). Thus, it was sought to identify what activities they carry out, the difficulties encountered, what contributed to their professional performance, and what vision they have about FHS and about themselves in the context. Based on the assumption that the practice of Nursing Technician is not still geared to completeness and that the developed actions by this professional are predominantly individual and curative. We know that FHS proposes the work organization as a team, with territory definition, prioritization of promotion actions, protection and recovery of the individual/family/community health, choosing as a central point the establishment of entails between the professionals and the same ones. However, the team work pass through interdisciplinary, tying and competence, starting making the difference in the way of thinking and doing health. To the accomplishment of this study were interviewed twenty one Nursing Technicians of Family Health Units from Sanitário Oeste district in Natal-RN, using semistructured instrument. From the analysis, three empiric categories emerged: starting from the first, The reality of a dream: what FHS is for the Nursing Technician, we obtained two classifications: one inherent to the own conception they have about FHS, nominated The realization of a dream in the possible and another that corresponds to what they think about FHS, while project that doesn't take place fully, denominated of The beauty of a dream that doesn't take place. The second category was The FHS: a dream built in the daily of Nursing Technician treats of the day by day information of that professional; the activities they perform and how those are established. This created three other items, to know: The role of a Nursing Technician: a project that became routine; The pre-determined role of a Nursing Technician: the scale as factor of (non-)autonomy; and, Knowledge about the practice in FHS: challenges that are presented to the role of Nursing Technician. The third category, denominated of Charms and disenchantment in the beginning of a new practice, it is related to the facilities or difficulties in professional's actuation and how he sees himself in the context. From it emerged the "flowers" and the "thorns" found on the construction of a dream, which gave this study the title. The results indicate that, being considered the characteristics of researched professional category, it becomes fundamental the resizing of labor relations in FHS, being imperative that new glances is conducted, so that the way as those Nursing Technicians interacts with the families can become compatible, together with the team, as well as to return the attention for their possibilities and limits in face of the work process in FHS. Besides, it is necessary changes in the professional formation, so that it can guarantee the conceptual bases in the construction of new practices, seeking to answer to the model of current attention.